IMPLEMENTATION OF PLAY THERAPY METHOD IN ISLAMIC COUNSELLING GUIDANCE FOR EARLY CHILDHOOD DEVELOPMENT - Arifin, Isep Zainal; Saadah, Hanifah (Universitas Islam Negeri Mataram, 2025)
Play therapy is an approach that has been proven effective in helping children overcome emotional, social, and behavioural challenges. This article examines the integration of play therapy in the context of Islamic counselling to support early childhood development. This study uses a descriptive qualitative method with literature analysis and interviews with Islamic counselling practitioners. The study results indicate that play therapy can be harmoniously adapted to Islamic values through a compassion-based approach, parental involvement, and applying spiritual principles appropriate to child development.Techniques such as Islamic storytelling, educational games, and creativity-based activities are integrated to build children's cognitive, emotional, and spiritual skills. This approach helps children overcome problems and form Islamic character early on. The implications of this study emphasise the importance of special training for counsellors in implementing Islamic-based play therapy, as well as collaboration between families and educational institutions to maximise results. This article makes an important contribution to developing innovative Islamic counselling methods relevant to the needs of child development in the modern era.